Gender Differences in the Relationship between Methamphetamine Use and High-risk Sexual Behavior among Prisoners: A Nationwide, Cross-sectional Survey in Japan. Issue 1 (1st January 2022) - Shimane, Takuya; Takahashi, Masaru; Kobayashi, Michiko; Takagishi, Yuriko; Takeshita, Yoshiko; Kondo, Ayumi; Omiya, Soichiro; Takano, Youichi; Yamaki, Mayuko; Matsumoto, Toshihiko
ABSTRACT: This study aimed to examine the relationship between methamphetamine (MA) use and high-risk sexual behavior among newly incarcerated prisoners in Japan. We conducted a secondary analysis using cross-sectional survey data, which constituted a nationwide prison sample surveyed between July and November 2017. In total, 699 participants (462 male and 237 female prisoners), who completed the self-administered questionnaire during imprisonment were recruited for the study. The prevalence of high-risk sexual behaviors was as follows: inconsistent condom use (78.4% male, 81.7% female), multiple sexual partners (61.3% male, 41.3% female), history of sexually transmitted diseases (14.1% male, 23.6% female), and trading sex for drugs (15.6% male, 17.7% female). A logistic regression analysis showed that MA use during sex increased the likelihood of high-risk sexual behavior in both male (adjusted odds ratio [AOR] = 5.86; 95% confidence interval [CI] = 3.41–10.07) and female prisoners (AOR = 2.58; 95% CI = 1.33–5.00). Additionally, in female prisoners, a history of sharing MA injection (AOR = 1.60; 95% CI = 1.06–2.42) increased high-risk sexual behavior. Our results indicate that harm reduction programs tailored according to the specific necessities of each gender to reduce high-risk sexual behaviors among MA users should be included in Japanese drug policies.